Agitation and aggression in people living with dementia and mild cognitive impairment in shared-housing arrangements – validation of a German version of the Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) - Kratzer, André; Scheel-Barteit, Jennifer; Altona, Janissa; Wolf-Ostermann, Karin; Grässel, Elmar; Donath, Carolin (Health and Quality of Life Outcomes, 2023)
Background: The Cohen-Mansfield Agitation Inventory-Short Form (CMAI-SF) is a 14-item scale for assessing agitation and aggression, derived from the original 29-item CMAI, and completed by a proxy. Because the CMAI-SF has not yet been validated in German language, the aim of this study is to explore its construct validity. Methods: Baseline data from a cluster-randomized trial to evaluate a non-pharmacological complex intervention for people living with dementia (PlwD) and mild cognitive impairment (MCI) were analyzed. The study sample consisted of 97 shared-housing arrangements (SHAs) in Germany, comprising N = 341 residents with mild to severe dementia and MCI. Trained nursing staff collected data by proxy-rating the CMAI-SF, Neuropsychiatric Inventory-Nursing Home Version (NPI-NH), and QUALIDEM. They also conducted the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Results: In an exploratory factor analysis, three factors emerged: “aggressive behavior”, “verbally agitated behavior”, and “physically non-aggressive behavior”. The CMAI-SF total score showed good internal consistency (α =.85), and the factors themselves showed adequate internal consistency (α =.75/.76/.73). The CMAI-SF showed convergent validity with the NPI-NH agitation item (r =.66) and the NPI-NH “agitation & restless behavior” factor (r =.82). Discriminant validity was confirmed by a low (r =.28) correlation with the NPI-NH apathy item. Quality of life decreased significantly with agitation, as the CMAI-SF showed a moderate negative correlation with the QUALIDEM total score (r = -.35). Conclusions: The 14-item CMAI-SF is a time-efficient, reliable, and valid assessment instrument. Three factors emerged that were similar to those already found in nursing home samples for the original CMAI and the CMAI-SF and in day care samples for the CMAI-SF. The findings provide preliminary evidence that the CMAI-SF can be used instead of the CMAI to reduce time, costs, and burden in future trials. Trial registration: The DemWG study from which data were used to draft this manuscript was prospectively registered on 16 July 2019 at ISRCTN registry (ISRCTN89825211).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Aggression; Agitation; CMAI; CMAI-SF; Cohen-Mansfield Agitation Inventory; Dementia; Mild cognitive impairment; Reliability; Shared-housing arrangements; Validity

Predictors of falls and hospital admissions in people with cognitive impairment in day-care: role of multimorbidity, polypharmacy, and potentially inappropriate medication - Scheel, Jennifer; Luttenberger, Katharina; Grässel, Elmar; Kratzer, André; Donath, Carolin (BMC Geriatrics, 2022)
Background Multimorbidity, polypharmacy, and potentially inappropriate medication (PIM) pose challenges for the care of people with cognitive impairment. The aim of the present study is to explore whether multimorbidity, polypharmacy, and PIM predict falls and hospital admissions in a sample of people with cognitive impairment in day-care centers in Germany. Methods We used data from the German day-care study (multicenter longitudinal study, n = 433). Multimorbidity was defined as >= 2 chronic diseases. Polypharmacy was defined as prescriptions to >= 5 drugs. Potentially inappropriate medication was defined as scoring on the PRISCUS list. Binary logistic regression analyses were computed to determine whether multimorbidity, polypharmacy, and potentially inappropriate medication at t0 predicted falls and hospital admissions as outcomes at t1 (six months later). Results The rate of multimorbidity and polypharmacy was 87.8% and 60.3%, respectively. 15.9% of the people with cognitive impairment received PIM / PRISCUS-listed drugs, 43.6% ACB-listed drugs, and 52.7% CNS depressant drugs. Falls and hospital admissions during follow-up were prevalent in 19.4% and 24.7% of the people with cognitive impairment. Both were significantly predicted by the total number of drugs (falls: OR = 1.152, p = 0.001, overall model: p < 0.001; hospital admissions: OR = 1.103, p = 0.020, overall model: p = 0.001), even if regression analyses were controlled for the number of comorbidities. Conclusions Polypharmacy and potentially inappropriate medication are highly prevalent in people with cognitive impairment in German day-care centers. The number of drugs and appropriateness of medication seem to be crucial for the risk of falls and hospital admissions. Polypharmacy and PIM should be critically reviewed by healthcare providers and avoided as much as and whenever possible.
CRIS-Team WoS Importer:2022-08-26

Predictors of institutionalization in users of day care facilities with mild cognitive impairment to moderate dementia - Spiegl, Klara; Luttenberger, Katharina; Grässel, Elmar; Becker, Linda; Scheel, Jennifer; Pendergrass, Anna (BMC Health Services Research, 2021)
Background: Most people with dementia wish to remain at home for as long as possible. Therefore, it is important to know the predictors of institutionalization, especially those that can be influenced. The aim of the present study is to identify predictors of the institutionalization of people with mild cognitive impairment (MCI) to moderate dementia who attend day care facilities (DCFs) throughout Germany.
CRIS-Team WoS Importer:2021-10-01

RISK REDUCTION OF HOSPITAL ADMISSIONS FOR PEOPLE WITH DEMENTIA IN SHARED-HOUSING ARRANGEMENTS: THE DEMWG STUDY - Wolf-Ostermann, Karin; Stiefler, Susanne; Schmidt, Annika; Friedrich, Anna-Carina; Grässel, Elmar; Donath, Carolin; Scheel, Jennifer; Kratzer, André (INNOVATION IN AGING, 2022)
CRIS-Team WoS Importer:2023-03-10

The DemWG study: reducing the risk of hospitalisation through a complex intervention for people with dementia and mild cognitive impairment (MCI) in German shared-housing arrangements: study protocol of a prospective, mixed-methods, multicentre, cluster-randomised controlled trial - Kratzer, André; Scheel, Jennifer; Wolf-Ostermann, Karin; Schmidt, Annika; Ratz, Katrin; Donath, Carolin; Grässel, Elmar (BMJ Open, 2020)
INTRODUCTION: Shared-housing arrangements (SHAs) are small, home-like care environments in Germany. Residents are predominantly people with dementia. The risk for all-cause hospitalisation is consistently higher for people with dementia compared with people without dementia and there is currently no evidence-based intervention to reduce the risk of hospitalisation. Thus, the DemWG study investigates whether a complex intervention is effective in reducing hospitalisation (primary outcome), behavioural and psychological symptoms of dementia and falls and for stabilising cognitive functioning and quality of life in people with dementia and mild cognitive impairment (MCI) in German SHAs. METHODS AND ANALYSIS: Based on the UK Medical Research Council framework 'Developing and evaluating complex interventions', a prospective, mixed-methods, multicentre, cluster-randomised controlled trial combining primary and secondary data analyses as well as quantitative and qualitative research methods is being conducted. The intervention consists of three parts: (A) education of nursing staff in SHAs; (B) awareness raising and continuing medical education (CME) of general practitioners; (C) multicomponent non-pharmacological group intervention MAKS-mk+ ('m'=motor training; 'k'=cognitive training; '+'=fall prevention) for people with dementia and MCI. Randomisation is stratified by the German federal states and type of setting (rural vs urban). Neither the trained professionals nor the participants are blinded. Data are collected at baseline and after 6, 12 and 18 months with standardised instruments. Quantitative data will be analysed by multivariate analyses according to the general linear model, qualitative data using qualitative content analysis. Recruitment is still ongoing until 31 December 2020. ETHICS AND DISSEMINATION: All procedures were approved by the Ethics Committee of the University of Bremen (Ref. 2019-18-06-3). Informed consent will be obtained before enrolment of participants. Due to findings of previous randomised controlled trials, serious adverse events are not expected. Results will be disseminated in peer-reviewed journal publications and conference presentations. TRIAL REGISTRATION NUMBER: ISRCTN89825211.
CRIS-Team Scopus Importer:2020-12-11
Keywords: delirium & cognitive disorders; dementia; geriatric medicine